Diabetic Macular Edema Before and After Intravitreal Triamcinolone Injection - Ramezani, Alireza (The Korean Ophthalmological Society, 2007)
PURPOSE: To compare intravitreal triamcinolone acetonide (IVT) versus natural course in refractory diabetic macular edema. METHODS: In a prospective interventional case series, twenty five eyes with refractory DME which had been allocated to the sham group of a previous clinical trial underwent new examination and optical coherence tomography about 9 months after their first enrollment. Twenty eyes that met the inclusion criteria, visual acuity (VA) < 20/50 and central macular thickness (CMT) > 200 μm, were treated by 4 mg IVT. Evaluations were repeated at 2 and 4 months post-injection to imitate the similar examination intervals after sham injection. Corrected visual acuity and macular thickness changes following IVT were compared to the corresponding changes after sham injection (the natural course). RESULTS: Visual acuity changes within and between each period were not statistically significant. Visual acuity decreased 0.08 & 0.09 logMAR by 2 months and 0.06 & 0.04 logMAR by 4 months after sham and IVT injections, respectively. The changes of macular thickness after IVT and sham intervention were not meaningful either. However, the difference between thickness changes by 4 months (52±50 μm increase after sham vs. 262±115 μm reduction after IVT) was significant (P=0.014). CONCLUSIONS: Concerning macular thickness, IVT has beneficial effect on refractory diabetic macular edema as opposed to observation. However, considering visual acuity, it does not induce significant difference in comparison to the natural course of the disease.